Immune-Related Adverse Events Associated With Immune Checkpoint Inhibitors for Advanced Non-small Cell Lung Cancer: A Network Meta-Analysis of Randomized Clinical Trials - Weidong Zhang; Jingjing Gu; Chunming Bian; Guanhong Huang (Frontiers Media S.A., 2021)
Objective: This network meta-analysis will provide a complete toxicity profile, toxicity profile, and safety ranking of immune checkpoint inhibitors (ICIs) for treatment of advanced non-small cell lung cancer (NSCLC).Methods: We found 12 phase II or III randomized clinical trials (RCTs) including 8,453 patients with NSCLC by searching Pubmed, Embase, and ClinicalTrials.gov. Risk ratios (RRs) and 95% confidence interval (CI) were used to compare the rate of immune-related adverse events (irAEs) for different ICIs-based treatments using pairwise and network meta-analysis with random effects.Results: For dermatologic irAEs, the corresponding ranking of incidences of the seven groups from high to low was: nivolumab + ipilimumab (97.4%), pembrolizumab (80.1%), nivolumab (67.1%), pembrolizumab + platinum (43.3%), atezolizumab + platinum (39.9%), durvalumab (17.5%), platinum-based chemotherapy (4.7%). For colitis, the corresponding ranking of incidences of the six groups from high to low was: atezolizumab + platinum (77.1%), nivolumab (67.3%), pembrolizumab (60.5%), durvalumab (45.2%), pembrolizumab + platinum (41.4%), platinum-based chemotherapy (8.5%). For endocrine irAEs, the corresponding ranking of incidences of the seven groups from high to low was: nivolumab + ipilimumab (79.1%), durvalumab (69.1%), pembrolizumab (61.9%), atezolizumab + platinum (60.4%),nivolumab (45.7%), pembrolizumab + platinum (33.5%), platinum-based chemotherapy (0.3%). For pneumonitis, the corresponding ranking of incidences of the seven groups from high to low was: pembrolizumab (99.3%), pembrolizumab + platinum (65.1%), durvalumab (62.2%), atezolizumab + platinum (56%), nivolumab (35.9%), platinum-based chemotherapy (18.1%),atezolizumab (13.3%). For hepatitis, the corresponding ranking of incidences of the six groups from high to low was: pembrolizumab (71.2%), pembrolizumab + platinum (64.3%), durvalumab (56.4%), atezolizumab + platinum (53.8%), nivolumab (44.5%), platinum-based chemotherapy (9.8%).Conlusion: In addition to platinum-based chemotherapy, durvalumab for dermatologic and liver irAEs, pembrolizumab for gastrointestinal irAEs, pembrolizumab + platinum for endocrine irAEs, and atezolizumab for pneumonitis may be associated with lower rates of irAEs than other immune-based regimens. Nivolumab + ipilimumab for dermatologic and endocrine irAEs, atezolizumab + platinum for colitis, and pembrolizumab for pneumonitis and hepatitis may be associated with higher rates of irAEs.